THE INFLUENCE OF TRAINING AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE - Putri, Aulia; Harini, Sri; Ismartaya, Ismartaya (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
A company can be said to be successful when the performance of the company's employees is good. Factors that influence employee performance are training, career development and employee engagement. This research aims to determine the influence and response to training, career development, employee engagement and employee performance. This research method is quantitative research with a simple random sampling technique. Data were collected through distributing questionnaires which were tested through validity, reliability, multicollinearity, heteroscedasticity, coefficient of determination, t test, and Sobel tests. The results of this research are that employee performance and employee involvement are in the quite high category, training and career development are in the quite good category. In addition, training and career development have a direct effect on employee engagement and have an indirect effect on employee performance through employee engagement.